The Selected Letters of Lewis Carroll - Carroll, Lewis. author. aut Link
XXI, 303 p.
Keywords: Lewis Carroll is one of the world's best-loved writers. His immortal Wonderland and delightful nonsense verses have enchanted generations of children and adults alike. The wit and imagination, the wisdom, sense of absurdity and sheer fun which fill his books shine just as clearly from the many letters he wrote. '...each is a miniature Wonderland... They reveal a truly delightful man...the combination of intense goodness and unselfishness with a magic, nonsense wit is unique'. The Scotsman '...a magnificent collection of delightful and entertaining letters reflecting all that was embraced in that remarkable character...all his charm, inventive fun, wisdom, generosity, kindliness and inventive mind'. Walter Tyson, Oxford Times.